Analysis of Laboratory Safety Protocols and Efficiency in Undergraduate Chemistry Laboratories: A Case Study of Q2 Laboratory - Asmari, Ali Ahmed; Alahmari, Faisal Abdullah; Alanazi, Sultan Bader; Alasmari, Abdullah saad; Alqahtani, Ayman saeed (Journal of Neonatal Surgery, 2025)
This study investigates the implementation of safety protocols and operational efficiency in undergraduate chemistry laboratories, with specific focus on the Q2 Chemistry Laboratory. Through a mixed-methods approach combining observational data, survey responses from 87 students and 12 laboratory instructors, and performance metrics analysis, this research evaluates the effectiveness of current laboratory management practices. Results indicate that while safety compliance rates are high (92.3%), several operational inefficiencies were identified, including equipment distribution bottlenecks and waste management procedures. Implementation of a digital laboratory management system resulted in a 24.7% reduction in experiment preparation time and a 31.2% improvement in resource utilization. This paper presents recommendations for optimizing undergraduate chemistry laboratory operations while maintaining rigorous safety standards. These findings contribute to the growing body of literature on laboratory education management and provide empirical support for technology-enhanced laboratory administration in undergraduate chemistry education.